Effects of the asynchronism of ground motion on the longitudinal behaviour of a circular tunnel. (December 2018) - Fabozzi, S.; Bilotta, E.; Yu, H.; Yuan, Y.
Highlights: Effect of asynchronous of ground motion compared with the synchronous case. The asynchronous tunnel motion affects the structural response of the tunnel lining. The asynchronous induces axial force along the tunnel axis, bending and shear force in the horizontal plane. Effect of the tunnel geometry and the direction of the incident wave on the tunnel internal forces. Abstract: The seismic performance of underground tunnels is affected by some significant factors mostly depending on the seismic loading conditions, the tunnel structure in interaction with the surrounding soil and the three dimensional geometry of the tunnel and the soil stratigraphy. The paper addresses the problem of underground tunnels when subjected to asynchronous seismic shaking along the axis in comparison with the synchronous case that is usually considered in the tunnels design. The study also includes the effect of the curved shape of the tunnel axis, the sudden change of dynamic impedance along its axis, the direction of the propagating wave and the effect of the initial state of stress induced by the excavation process. A finite element model able to catch the main deformation patterns of a tunnel subjected to non-uniform seismic load, coupling the axial and longitudinal deformations has been defined in Plaxis 3D. The numerical model has been first validated with a simplified benchmark case where the soil behaves elastically, and afterwards on the real case of the Metro Line 6 of Naples, assuming a more sophisticated constitutive model for the soil. The results of the 3D full dynamic analyses show the effect of the ground motion asynchronism on the distributions of internal forces in the tunnel lining.